PERKEMBANGAN KOMSEL PELAJAR DALAM PERTUMBUHAN ROHANI JEMAAT GBI GRAHA PENA JAKARTA - Imron Widjaja (The Way Jurnal Teologi dan Kependidikan, 2019)
This study aims to explore the influence of student cell groups in church growth in GBI Graha Pena. Cell groups as a small group community that is a means of fostering, guiding and guiding and disciplining students specifically teaching. In accordance with the stage of growth and development, where the age of the student is very wrong range in association and makes himself not grow in spiritual life. This student cell group becomes a tool and means of realizing God's will for the spiritual growth of the GBI Graha Pena congregation. The method in this study uses qualitative and is carried out for GBI Graha Pena Sunday School children. The results showed that students have enthusiasm and high willingness. to participate in student cell groups and influence growth in their spiritual lives.